Influence to the Audience as a Communicative Function in Brand Management - Juozėnaitė, Eglė (Socialiniai tyrimai, 2021)
Relevance and problem of the topic. Exploring the influence of brand communication on different audiences is a complex and responsible process because the same communicated message to different audiences can be understood differently. An improperly communicated message may not reach the audience, be misunderstood, or provoke a hostile reaction, however, a properly chosen communication message may have the desired influence to the audience. How to communicate with different audiences and what methods to choose are especially important in today’s rapidly changing context.The problem analyzed in this article can be defined by the following questions: How to communicate with the audience? What influences to choose from? Based on this information, it will be possible to continue research in the field of public relations management to reveal the influence of brand communication on the audience, it can help brands to gain a competitive advantage in the markets and create greater added value.Problems. It is not entirely known what impact brand communication has on audiences. It is important for brands not only to create a brand image but also to find and choose the most appropriate ways to communicate with the audience so that individuals receive the communication message sent to them in the most acceptable and understandable ways. Improper communication, inaccurately chosen methods of communication with the audience can lead to undesirable consequences. The message sent by the brand can be misunderstood and interpreted, it can lead to undesirable negative consequences and cause reputational crises, leading to significant psychological, social, financial losses. Properly selected communication can help brands gain a competitive edge in the markets and create greater added value.Objective. To review and analyze the ways of brand’s communication, which aims to influence the audiences.The object: the influence of communication in brand managementTasks: 1) To analyze the concept of the brand; 2) To analyze the concept of the audience; 3) To review the ways of brand communication influence.Methods of comparative theoretical analysis and synthesis of the literature, generalization.Brand management consists of the role of the brand and the symbolic elements of the brand (brand name, logo, text). The brand is the most durable asset of the company. Good results are achieved by companies that are able to choose a brand strategy that meets consumer expectations. Brands can also make the influence by creating compelling knowledge and news by communicating in ways that reduce cognitive stress. In order to influence other people, it is possible to do so by appealing to the feelings of the audience, realizing the main emotions - anger, fear, sadness, feeling of happiness, disgust. It is important to monitor what kind of emotions brand communication causes to the audience, pay attention to the feedback. An audience can be interpreted as everything that an individual or organization communicates. In order to present news to the audience as convincingly and persuasively as possible, it is important to segment the audience and create a description of the target user.
Keywords: brand; influence; audience; communication; brand management